Noise pollution and its impact on the quality of life of the urban population of the city of San Gabriel - Meneses Pastaz, Jeaneth Alexandra; Ávila Treviño, Jazmin Anai (SATHIRI, 2024)
Noise pollution is a problem generated by the lifestyle and cultural level of a population, which for many is part of their daily life that affects everyone but few act to stop it. The city of San Gabriel is not a city outside this world reality, fixed sources [FFR] and mobile sources [FMR] of noise have a negative impact with noise emissions into the environment. Applying a descriptive field investigation with techniques such as direct observation-monitoring, surveys, and interviews to assess the impact of noise on the exposed population, 152 preselected FFRs and 363 FMRs were monitored at the vehicle inspection center, complemented by the monitoring of 52 road intersections. of greater random vehicular flow through the 15-second technique with 10 samples using a class 1 integrating sound level meter, with an A and C weighting filter, generating a noise map through IDW and Kriging geospatial interpolation, identifying that 52% of the emissions of FFR exceeded the values allowed according to legal regulations and where 53.4% were activities incompatible with the territory, reaching LKeq values of 70 dB for FMR, corroborating the perception of the population that demonstrated the correlation between the level of exposed noise and discomfort. caused by determining that San Gabriel presents noise pollution problems by FFR and FMR of moderate level, allowing the generation of a proposal to achieve a significant reduction in noise.
Keywords: Decibels; fixed sources; mobile sources; sound level meter; noise pollution